Characterization of the near native conformational states of the SAM domain of Ste11 protein by NMR spectroscopy - Gupta, Sebanti (2016)
The sterile alpha motif or SAM domain is one of the most frequently present protein interaction modules with diverse functional attributions. SAM domain of the Ste11 protein of budding yeast plays important roles in mitogen-activated protein kinase cascades. In the current study, urea-induced, at subdenaturing concentrations, structural, and dynamical changes in the Ste11 SAM domain have been investigated by nuclear magnetic resonance spectroscopy. Our study revealed that a number of residues from Helix 1 and Helix 5 of the Ste11 SAM domain display plausible alternate conformational states and largest chemical shift perturbations at low urea concentrations. Amide proton (H/D) exchange experiments indicated that Helix 1, loop, and Helix 5 become more susceptible to solvent exchange with increased concentrations of urea. Notably, Helix 1 and Helix 5 are directly involved in binding interactions of the Ste11 SAM domain. Our data further demonstrate that the existence of alternate conformational states around the regions involved in dimeric interactions in native or near native conditions.